1988
DOI: 10.1007/bf00256767
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine status after major trauma

Abstract: A prospective study of thiamine status in patients with severe injuries (injury severity scores greater than 12) showed that they all developed signs of severe thiamine deficiency on the basis of transketolase activity, the standard biochemical test for thiamine deficiency. This occurred within the first week after their injuries despite routine enteral or parenteral feeding including vitamin supplements. This may be due to increased requirements secondary to increased metabolic activity or increased cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Thiamin is a critical cofactor in the glycolysis and oxidation of carbohydrates for energy production. Despite thiamin supplementation in patients with severe injuries, severe thiamin deficiency developed within the first week of their injuries according to 1 study . Ten percent of critically ill patients with sepsis were found to have an absolute thiamin deficiency in 1 prospective study .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thiamin is a critical cofactor in the glycolysis and oxidation of carbohydrates for energy production. Despite thiamin supplementation in patients with severe injuries, severe thiamin deficiency developed within the first week of their injuries according to 1 study . Ten percent of critically ill patients with sepsis were found to have an absolute thiamin deficiency in 1 prospective study .…”
Section: Discussionmentioning
confidence: 99%
“…Despite thiamin supplementation in patients with severe injuries, severe thiamin deficiency developed within the first week of their injuries according to 1 study. 9 Ten percent of critically ill patients with sepsis were found to have an absolute thiamin deficiency in 1 prospective study. 10 According to another study, up to 20% of patients in the ICU were found to be thiamin deficient, and these patients had a much higher mortality rate (72%) than the overall mortality rate (50%).…”
Section: Thiaminmentioning
confidence: 99%
“…Infants are particularly vulnerable to the effects of thiamine deficiency in the first months of life, and exclusively breastfed infants of thiamine‐deficient mothers are at highest risk . Thiamine deficiency is also frequently observed in patients who are critically ill or in intensive care because of increased demand for thiamine (hypermetabolism) . In clinical practice, associated comorbidities and other risk factors, such as SAM with fever and shock and use of dextrose‐based intravenous fluid, further increase the risk of thiamine deficiency .…”
Section: Thiamine Deficiency and Its Consequencesmentioning
confidence: 99%
“…14 This suggests that low thiamine levels result from a combination of poor nutritional intake and increased catabolism in critically ill patients. Furthermore, if one uses the classic triad of mental status changes, opthalmoplegia and gait ataxia as a diagnostic indicator for WE, up to 90% of cases may be missed.…”
Section: Discussionmentioning
confidence: 99%